Compressive behavior and modelling of engineered cementitious composite (ECC) confined with LRS FRP and conventional FRP. (15th September 2021) - Yuan, Wan-Ying; Han, Qiang; Bai, Yu-Lei; Du, Xiu-Li; Yan, Zhi-Wei
Highlights: Axial compressive behavior of ECC columns wrapped with LRS FRP/conventional GFRP was presented. The effects of the FRP type and confinement stiffness were investigated. The compressive behavior between FRP-confined ECC and FRP-confined NC under the same confinement level was compared. Six existing theoretical confinement models were evaluated. A modified design-oriented model and a modified dilation model were established for FRP-confined ECC. Abstract: A combination of core engineered cementitious composite (ECC) and external fiber-reinforced polymer (FRP) composites can solve the problems of insufficient ductility and durability of normal concrete (NC) in adverse environments and improve bearing capacity. However, existing studies on the performance of ECC strengthened by FRP are very limited—particularly the research on large rupture strain (LRS) FRP-confined ECC. In this study, an experimental investigation of LRS FRP and conventional glass FRP-confined ECC cylinders with different confinement levels under axial compression is presented. It is found that the application of external FRP jackets leads to a significant improvement in the compressive strength and deformation of the core ECC. LRS FRP-confined ECC exhibits a higher ultimate deformation than conventional FRP-confined ECC. The dilation behavior, axial stress–strain behavior, and energy dissipation capacity between FRP-confined ECC and FRP-confined NC under the same confinement level are compared, and the former exhibits a significantly larger ductility and energy dissipation capacity than the latter. The results also indicate that most existing models are unable to accurately predict the compressive behavior of FRP-confined ECC. To address this, a dilation model and an axial stress–strain model of FRP-confined NC are modified to extend their application to FRP-confined ECC.